Legal Analysis of the Phenomenon of “No Viral No Justice”: in Law Enforcement and Legal Injustice in Indonesia - Fitriani, Nisa (Ultimate Journal of Legal Studies, 2025)
The phenomenon of "No Viral No Justice" in Indonesia reflects public dissatisfaction with the law enforcement system which is considered unresponsive. "No viral no justice" creates a negative stigma against law enforcement, which distinguishes between viral and non-viral law enforcement. Justice must be achieved not only because of the speed of information spread on social media but also information from the public without going through social media information. This emphasizes that victims must make their experiences viral so that their cases are revealed and law enforcement officers act more quickly in handling the viral case. Injustice in law enforcement against information spread quickly on social media is contrary to Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia that everyone has the right to receive the right to recognition, guarantees, protection and certainty of fair law and equal treatment before the law. This research method uses normative legal analysis with a qualitative approach that reviews more specific, planned and systematic objects through data. The results of this study describe the forms of law enforcement and legal injustice in Indonesia. It can be concluded that the role of the authorities is not fast in responding to cases that are not viral and are important for upholding justice from a legal perspective in Indonesia.